Neuronal Modulations in Visual Cortex Are Associated with Only One of Multiple Components of Attention - Luo, Thomas Zhihao; Maunsell, John H.R. (Neuron (Cambridge, Mass.), 2015)
Neuronal signals related to visual attention are found in widespread brain regions, and these signals are generally assumed to participate in a common mechanism of attention. However, the behavioral effects of attention in detection can be separated into two distinct components: spatially selective shifts in either the criterion or sensitivity of the subject. Here we show that a paradigm used by many single-neuron studies of attention conflates behavioral changes in the subject’s criterion and sensitivity. Then, using a task designed to dissociate these two components, we found that multiple aspects of attention-related neuronal modulations in area V4 of monkey visual cortex corresponded to behavioral shifts in sensitivity, but not criterion. This result suggests that separate components of attention are associated with signals in different brain regions and that attention is not a unitary process in the brain, but instead consists of distinct neurobiological mechanisms. •A commonly used attention paradigm conflates two distinct components of attention•We dissociated these components using a specifically designed task•Neuronal signals in visual cortex correspond to one component, but not the other•The results suggest that separate brain areas underlie distinct mechanisms of attention Luo and Maunsell show that the neuronal modulations in visual cortex correspond to only one of multiple components of attention. This result suggests that different brain structures underlie separate mechanisms of attention and that attention is not a unitary process.